2021
DOI: 10.1002/ange.202110102
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Phosphorus‐Directed Borylation of C(sp2)−H Bonds

Abstract: Spectacular progress has recently been achieved in transition metal-catalyzed CÀHb orylation of phosphines as well as directed electrophilic CÀHb orylation. As shown here, P-directed electrophilic borylation provides anew,straightforward,a nd efficient access to phosphine-boranes.I to perates under metal-free conditions and leverages simple,r eadily available substrates.I ti sa pplicable to ab road range of backbones (naphthyl, biphenyl, N-phenylpyrrole,b inaphthyl, benzyl, naphthylmethyl) and gives facile acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…Very recently, Bourissou and co-workers reported that a phosphine moiety serves as a directing group for the electrophilic borylation of a proximal CÀ H bond to give phosphine-boranes (Scheme 21a). [99] Various phosphines having different backbones, such as naphthyl (74), biphenyl (75), N-phenylpyrrole (76), benzyl (77), and naphthylmethyl (78), were applicable to the reaction. At nearly the same time, Wang, Shi, and co-workers also reported the same transformation (Scheme 21b).…”
Section: In-built Directing-group-assisted Metal-free Cà H Borylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Bourissou and co-workers reported that a phosphine moiety serves as a directing group for the electrophilic borylation of a proximal CÀ H bond to give phosphine-boranes (Scheme 21a). [99] Various phosphines having different backbones, such as naphthyl (74), biphenyl (75), N-phenylpyrrole (76), benzyl (77), and naphthylmethyl (78), were applicable to the reaction. At nearly the same time, Wang, Shi, and co-workers also reported the same transformation (Scheme 21b).…”
Section: In-built Directing-group-assisted Metal-free Cà H Borylationmentioning
confidence: 99%
“…Along with heterocycles, a phosphine moiety has also been used as an auxiliary for metal‐free directed C−H borylation. Very recently, Bourissou and co‐workers reported that a phosphine moiety serves as a directing group for the electrophilic borylation of a proximal C−H bond to give phosphine‐boranes (Scheme 21a) [99] . Various phosphines having different backbones, such as naphthyl ( 74 ), biphenyl ( 75 ), N ‐phenylpyrrole ( 76 ), benzyl ( 77 ), and naphthylmethyl ( 78 ), were applicable to the reaction.…”
Section: Directing‐group‐assisted C−h Borylationmentioning
confidence: 99%
“…Among various modification approaches, the C–H functionalization of simple biarylphosphines is often an efficient, atom- and step-economical strategy. Alkylation, alkenylation, , arylation, borylation, and silylation of biarylphosphines have been carried out in recent years. Despite achieving great success, further developing the methodology to extend ligand libraries and searching for alternative coupling partners are still highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have developed the Ru-catalyzed ortho C–H borylation reaction of arylphosphines with HBpin to afford o -phosphinophenylboronic acid pinacol esters in high yields. 11,12 In our continuous research on the utilization of the borylation products, it was found that the treatment of ( o -diphenylphosphino)phenylboronate 1a with 1.0 equiv. of ZnEt 2 in toluene at room temperature afforded triphenylphosphine in 79% yield after acidic hydrolysis (Table 1, entry 1).…”
mentioning
confidence: 99%